Adaptação de um programa de mindfulness em formato online, individual e síncrono para profissionais da saúde: estudo de viabilidade - Giacometti, Cilene Aparecida (2023)
Healthcare professionals are increasingly suffering from the consequences of occupational stress, therefore, accessible and effective interventions are recommended for the prevention of mental and emotional illness. Aligned with this scenario, there is growing interest among these professionals in Mindfulness-based interventions. This led us to conduct this study of adaptation and feasibility verification based on MBI of MBHP in an online, individual, and synchronous format. With this study, we aim to fill some of the gaps in the literature regarding online, individual, and synchronous MBIs’ format. Conclusion: Female healthcare professionals are more likely to adhere to this type of MBI. The results observed pre and post-intervention are compatible with other studies that point out the effectiveness of an in-person and group format MBI for reducing both occupational stress and compassion fatigue. The potential impact of the proposed model shows that participants have learned stress management, improved emotional symptoms, reduced suffering caused by mental rumination and increased positive outlook on life. Regarding feasibility, reports indicate that this is an accessible program due to its low cost, ease of understanding, and enlightening interaction between the instructor and the participant. The acceptance of Mindfulness practice, which was new to most participants, and an opportunity to understand how to break free from daily automatism. They realized that through Mindfulness training, it was possible to reconnect with their values and life purposes, as well as to become more self-aware. With the results, discussion and conclusion presented, future studies can be developed, strengthening the network of professionals working with the MBHP or other MBIs, teachers and instructor training centers of Mindfulness in Brazil, Latin America, and Europe.